GE_GERICHTE P/9883/2015 vom 27. Mai 2016 - GE Cour de justice (2016)
IN DUBIO PRO REO ; PRÉSOMPTION D'INNOCENCE ; SÉJOUR ILLÉGAL ; DIRECTIVE 2008/115/CE | LEtr115.1 B; CEDH6.2; Directive sur le retour 2008/115/CE